The Arctic front of the global hybrid warfare - E O. Labetskaya (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The role and significance of the Arctic in international relations of the late 20th and early 21st centuries have undergone serious changes, and so have their assessments in the academic literature. To date, the Arctic has already turned into the scene of bitter international rivalry, albeit not yet a theater of military operations. In order to provide a better understanding of the scale, dynamics, and potential consequences of these developments, the author examines them through the lens of the hybrid warfare concept. The first section provides a thorough review of the key approaches to the definition of the hybrid warfare and its specific features. The author pays special attention to the NATO’s theoretical advances in the methods of the hybrid warfare and their practical implementation in the Arctic region. The second section examines the specific forms and manifestations of hybrid warfare in the Transarctic. The researcher notes that the population of the islands of Svalbard and Wrangel is exposed to a remarkably large-scale hostile hybrid influence from the NATO countries, and concludes that Russophobic narratives peddled to the peoples of the Subarctic pose a serious risk to regional stability. The author argues that in order to counter hybrid threats from the collective West, Russia needs to develop a comprehensive Arctic strategy. The latter should include, inter alia, an effective system for monitoring geopolitical threats not only against Russia, but also against its BRICS+, SCO, EAEU, CSTO partners; measures to strengthen cooperation with Eurasian, international and intergovernmental structures and business communities unyielding against sanctions pressure; programs for the development of indigenous peoples aimed at preserving their civilizational identity.